2020
DOI: 10.31557/apjcp.2020.21.8.2381
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Tissue BRCA Gene Mutation in Ovarian, Fallopian Tube, and Primary Peritoneal Cancers: A Multi-Institutional Study

Abstract: Epithelial ovarian cancer (EOC) is the 6th most common cancer among Thai females with the age

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Concerning the distribution of variants among the different histotypes, 10 high-grade serous subtypes (26.3%) out of 38 individuals revealed a BRCA1/2 pathogenic mutation, and three carried a pathogenic mutation in one of the HR genes. These results further confirm previous literature reports [ 6 , 42 , 43 , 44 ]. Remarkably, four (40%) endometrioid cancers out of ten in our cohort were found to harbor three deleterious mutations in BRCA1 and 1 in BRCA2 .…”
Section: Discussionsupporting
confidence: 93%
“…Concerning the distribution of variants among the different histotypes, 10 high-grade serous subtypes (26.3%) out of 38 individuals revealed a BRCA1/2 pathogenic mutation, and three carried a pathogenic mutation in one of the HR genes. These results further confirm previous literature reports [ 6 , 42 , 43 , 44 ]. Remarkably, four (40%) endometrioid cancers out of ten in our cohort were found to harbor three deleterious mutations in BRCA1 and 1 in BRCA2 .…”
Section: Discussionsupporting
confidence: 93%
“…Among these included articles, 50 studies 6,7,9-12,18-61 evaluated the relationship between patients with BRCAms and the clinical features of ovarian cancer, and 22 studies 6,7,9,11,12,21,28,32,[38][39][40]44,45,48,49,52,53,[58][59][60]62,63 evaluated the relationship between patients with BRCAms and surgical outcomes. Also, 48 studies , [6][7][8][9][10][11][12]18,21,[26][27][28][29][30][32][33][34][35][36][37][38][39][40][41][44][45][46][47]…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-three studies [6][7][8][9][10][11][12]18,[27][28][29][32][33][34][35][36][37][38][39][40][41][46][47][48]52,54,57,60,63,65,66,68,69 provided OS data of patients with BRCA1/BRCA2 mutations. Heterogeneity was observed among the 33 studies (I 2 = 50.3%); therefore, a random effects model was used.…”
Section: Meta-analysis Of Brca1/brca2 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this uncertainty in the estimate proportion, germline BRCA1/2 PVs were detected in all histological subtypes of OC. Also, in seven studies that incorporated an extra round of pathological revision in their study design, germline BRCA1/2 PVs were identified in all histological subtypes [1,28,31,34,42,47,48].…”
Section: Proportion Of Germline Brca1/2 Pvs Per Histological Subtypementioning
confidence: 99%